2018
DOI: 10.1177/1534508418808365
|View full text |Cite
|
Sign up to set email alerts
|

False Discovery Rates When Engaging in Skill Versus Performance Deficit Analysis for Academic Instructional Planning

Abstract: Brief experimental analysis (BEA) is a well-researched approach to conducting problem analysis, where potential interventions are pilot tested using a single-subject alternating treatment design. However, its brevity may lead to a high frequency of decision-making errors, particularly in situations where one tested condition is rarely optimal for students (i.e., the base rate). The current study explored the accuracy of a specific variant of BEA, skill versus performance deficit analysis (SPA), across differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Christ and Vining (2006) mentioned the possibility of using a stratified item arrangement for SSM-CBM probes but suggested that a random item arrangement is likely sufficient due to the narrower content that is represented on such probes. However, others have expressed concerns related to the precision of SSM-CBM time-series data for instructional decision making (Methe et al, 2015; Solomon et al, in press). Stratifying within SSMs could potentially be a feasible way to increase precision on these probes by increasing the consistency of difficulty across their various iterations.…”
Section: Item Arrangementmentioning
confidence: 99%
“…Christ and Vining (2006) mentioned the possibility of using a stratified item arrangement for SSM-CBM probes but suggested that a random item arrangement is likely sufficient due to the narrower content that is represented on such probes. However, others have expressed concerns related to the precision of SSM-CBM time-series data for instructional decision making (Methe et al, 2015; Solomon et al, in press). Stratifying within SSMs could potentially be a feasible way to increase precision on these probes by increasing the consistency of difficulty across their various iterations.…”
Section: Item Arrangementmentioning
confidence: 99%
“…These results are consistent with research in reading BEAs, which has also used a 20% criterion to determine if an intervention is more effective than baseline and visual analysis to determine the most effective intervention overall (Daly et al, 1999; Jones & Wickstrom, 2002; Noell et al, 2001). It has been suggested that more liberal decision-making criteria, such as the 50% criterion may be problematic in that it may result in students being over identified as having a performance-only deficit (Soloman, Dawes, Duhon, & Poncy, 2018). Recently, Soloman et al (2018) conducted an empirical analysis to determine which decision-making criterion would be most appropriate within a skill versus performance analysis and found that the 20% criterion is generally the most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that more liberal decision-making criteria, such as the 50% criterion may be problematic in that it may result in students being over identified as having a performance-only deficit (Soloman, Dawes, Duhon, & Poncy, 2018). Recently, Soloman et al (2018) conducted an empirical analysis to determine which decision-making criterion would be most appropriate within a skill versus performance analysis and found that the 20% criterion is generally the most appropriate. The findings of the current synthesis, along with the recent results of Soloman et al (2018), suggest that in future math BEA studies, a 20% criterion may be the most appropriate and can be used to develop consistency in decision-making procedures across math BEA studies.…”
Section: Discussionmentioning
confidence: 99%